Protection of Child Victims of Violence in Daycare: A Case Study in Palembang - Hasanah, Uswatun; Rahman, Dapa; Anjelina, Tri Cici; Agustin, Riri Sasta; Sapinah; Berlia, Fretty (Yayasan Bina Lentera Insan, 2026)
Violence against children in daycare centers has become a serious concern because children are a vulnerable group that requires special protection. This study aims to analyze the legal protection provided to child victims of violence in daycare centers, examine the role of daycare as a child care institution, and explore cases of child abuse occurring in Palembang City. This research employs a normative legal research method using a library research approach. The data used are secondary data obtained from the examination of legislation, books, scientific journals, and other relevant literature. Data were collected through documentation studies and analyzed using a descriptive qualitative method. The findings indicate that child protection is a shared responsibility of families, communities, daycare providers, and the government. Although daycare centers serve as institutions that support children's growth and development, cases of violence still occur due to weak supervision, inadequate caregiver competence, and the ineffective implementation of child protection systems. In Palembang City, incidents of violence against children in childcare institutions highlight the urgent need to strengthen monitoring mechanisms, improve caregiver quality, and enforce legal protections more effectively. These measures are essential to ensure the fulfillment of children's rights and to prevent similar incidents from occurring in the future.